2023
DOI: 10.1038/s41467-023-40436-1
|View full text |Cite
|
Sign up to set email alerts
|

A mosaic adeno-associated virus vector as a versatile tool that exhibits high levels of transgene expression and neuron specificity in primate brain

Abstract: Recent emphasis has been placed on gene transduction mediated through recombinant adeno-associated virus (AAV) vector to manipulate activity of neurons and their circuitry in the primate brain. In the present study, we created a novel vector of which capsid was composed of capsid proteins derived from both of the AAV serotypes 1 and 2 (AAV1 and AAV2). Following the injection into the frontal cortex of macaque monkeys, this mosaic vector, termed AAV2.1 vector, was found to exhibit the excellence in transgene ex… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 57 publications
1
2
0
Order By: Relevance
“…We have previously tested the DREADD excitability of striatal neurons in combination with hM3Dq and DCZ using FDG uptake as a marker and found that 1 µg/kg of DCZ increased striatal uptake by ∼10% ( Nagai et al, 2020 ; Kimura et al, 2023 ), a similar range to what we observed for PSAM4 requiring a 100-fold higher dose of PSEM in the current study. Assuming comparable expression levels because the same AAV vector was used at similar titers in these cases, DREADD/DCZ may have greater efficacy in activating striatal neurons, although generalization by direct comparison is still limited.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…We have previously tested the DREADD excitability of striatal neurons in combination with hM3Dq and DCZ using FDG uptake as a marker and found that 1 µg/kg of DCZ increased striatal uptake by ∼10% ( Nagai et al, 2020 ; Kimura et al, 2023 ), a similar range to what we observed for PSAM4 requiring a 100-fold higher dose of PSEM in the current study. Assuming comparable expression levels because the same AAV vector was used at similar titers in these cases, DREADD/DCZ may have greater efficacy in activating striatal neurons, although generalization by direct comparison is still limited.…”
Section: Discussionsupporting
confidence: 86%
“…In the current study, we used AAV2.1 vectors with a human synapsin promoter (hSyn) for neuron-specific transduction of PSAM4-5HT3 with or without fusion protein tags. The combination of AAV2.1, hSyn, and HA/FLAG tags has been used in this study and in previous hM4Di/hM3Dq DREADD studies with macaque monkeys ( Kimura et al, 2023 ; Miyakawa et al, 2023 ). As expected, our AAV construct successfully induced PSAM4-5HT3 expression in the striatum and MI cortex, as visualized by [ 18 F]ASEM-PET.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation